2009
DOI: 10.1897/ieam_2008-057.1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of fish community structure in a long‐term watershed‐scale study to address the aquatic ecosystem effects of pulp and paper mill discharges in four us receiving streams

Abstract: Physiological changes have been seen in individual fish exposed to pulp and paper mill effluent (PPME), but it is unclear whether community-level changes are seen in fish in PPME receiving waters. We conducted a study of 4 PPME receiving streams (Codorus Creek, PA, USA), the Leaf River (Forrest and Perry Counties, MS, USA), and the McKenzie and Willamette rivers (Lane County, OR, USA) over 9 y to assess temporal patterns in the type and relative abundance of fish species and measures of community structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
(77 reference statements)
1
11
0
Order By: Relevance
“…Various techniques for linking species occurrence to area now exist (Kunin, 1998; Ovaskainen & Hanski, 2003). Most of these are focused on terrestrial systems, but a growing number of investigators of fish communities now explicitly include scale in their analyses (Chick et al , 2004; Higgins & Strauss, 2008; Flinders et al , 2009; Kang et al , 2009; Strecker et al , 2011).…”
Section: Future Directionsmentioning
confidence: 99%
“…Various techniques for linking species occurrence to area now exist (Kunin, 1998; Ovaskainen & Hanski, 2003). Most of these are focused on terrestrial systems, but a growing number of investigators of fish communities now explicitly include scale in their analyses (Chick et al , 2004; Higgins & Strauss, 2008; Flinders et al , 2009; Kang et al , 2009; Strecker et al , 2011).…”
Section: Future Directionsmentioning
confidence: 99%
“…NCASI's LTRWS found that although changes in fish at the community level were variable across seasons and years, there were no effluent-related changes in species type and relative abundance at sites downstream of discharges relative to upstream sites (Flinders et al 2009c). …”
Section: Effluentmentioning
confidence: 99%
“…Similarly, Flinders et al (2009b) report on the examination of macroinvertebrate community structure and multimetric indices above and below paper mill discharges on each waterway, as well as large and small bodied fish community structure metrics. Flinders et al (2009c) report on sustain‐ability and reproductive viability of fish populations through long‐term multispecies community level monitoring. As an augmentation to this knowledge, Borton et al (2009) reports the results of full life cycle bioassays with the fathead minnow ( Pimephales promelas ) with each effluent.…”
Section: Editor's Notementioning
confidence: 99%